A green composite hydrogel based on cellulose and clay as efficient absorbent of colored organic effluent. (15th April 2019) - Wang, Qiyang; Wang, Yixiang; Chen, Lingyun
Highlights: A green composite hydrogel based on wood cellulose and clay is reported. Clay were well dispersed in the composite hydrogel network. Adsorption capacity of composite hydrogel can even reach 277 mg/g. The adsorption mechanism was studied and discussed. Abstract: This work has developed a convenient way of constructing wood cellulose and clay green composite hydrogel as efficient adsorbent of colored organic effluent. The optimized cellulose/montmorillonite(MTM) hydrogels showed excellent methylene blue (MB) absorption with the maximum capacity of adsorption (Qmax ) of 277 mg/g, which is not only higher than MTM alone, but also higher than many other natural clay composite adsorbents. Adsorption mechanism and kinetic studies that the physisorption was a major processing in MB absorption and the adsorption mainly occurred in the internal structure of composite hydrogel. This indicated that the MTM embedded inside played the most critical role for the MB dye adsorption. Owing to its biodegradability and excellent adsorption capacity, cellulose/MTM hydrogel has good potential for colored organic effluent treatment. The simple procedure and cost effective wood cellulose as raw material for the composite absorbent construction presented in this research are favorable for industrial applications.